Complex Care Curriculum: Evaluation and Management of Gastroesophageal Disease (GERD) in the Neurologically Impaired Child (NIC) - Amina Khan; Anil Darbari; Neha Shah; Priti Bhansali; Melanie Anspacher (Association of American Medical Colleges, 2014)
Abstract Introduction Children with special health care needs are increasingly prevalent in US hospitals. The pediatric hospitalist is often the primary provider of inpatient care for these patients. However, exposure to this patient population during training varies from provider to provider. No published educational curricula are specific to the inpatient care of this population. The Complex Care Curriculum's purpose is to build a multimodal educational curriculum for providers with the overall goal of improving inpatient care for this at-risk population. Methods This particular module focuses on gastroesophageal reflux disease (GERD) in neurologically impaired children (NIC). GERD is prevalent among NIC, and at this time, guidelines specifically for this patient population do not exist. This resource includes a multimedia, narrated PowerPoint show for asynchronous learning, a PowerPoint presentation adapted for didactic teaching, a facilitator guide, suggested multiple-choice questions with answer key, an evaluation tool, and a complete list of references and resources. The target audience is pediatric hospitalists and other general pediatric providers or trainees who care for medically complex children in an inpatient setting, although the module may also be applicable to health care providers in outpatient settings. Results The curriculum was implemented in 2012, and a pilot study of participants was conducted. Impact on knowledge, skills, and attitudes was assessed. Fourteen study participants completed the GERD evaluation and the management in NIC module. Of these participants, 100% either agreed or strongly agreed that the module was relevant to clinical practice, and 87% either agreed or strongly agreed that the module increased their comfort with the topic. All agreed that the learning format was appropriate to their learning needs. Based on this study, the module continues to be offered to trainees and new faculty to augment their knowledge and skills in this area. Discussion Although guidelines for GERD management in the general pediatric population are available, they do not specifically address the needs of NIC. Given the complexities of this high-risk population and the fact that GERD is prevalent within NIC, a resource that outlines the diagnostic workup and treatment options for GERD in NIC would be useful to providers. This particular resource serves as an introductory primer on evidence-based practices for GERD evaluation and management for pediatric hospitalists and pediatricians who serve as primary providers for NIC.